Egypt’s agrifood system: Transformation and environmental impacts - Diao, Xinshen; Ecker, Olivier; Fang, Peixun; Jones, Eleanor; Pauw, Karl; Raouf, Mariam; Steinhuebel-Rasheed, Linda; Thurlow, James (International Food Policy Research Institute, 2025)
Agrifood System Diagnostic series presentation prepared June 2025.